2009
DOI: 10.1159/000231885
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Oncology: How Far Have We Gone and What Are the Next Steps?

Abstract: Geriatric oncology is increasingly developing in Western countries as it is established that cancer peaks after 60 years of age, and the populations are inexorably aging. Aging is associated with a decrease in the use of chemotherapy, and some patients are therefore exposed to undertreatment. Comprehensive geriatric assessment is a composite of several scores that target the multidimensional aspects of the old person. With the use of comprehensive geriatric assessment, geriatricians and oncologists can tailor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 92 publications
0
7
0
1
Order By: Relevance
“…The US National Center for Health Statistics estimated that 84% of noninstitutionalized individuals aged ≥65 years are dependent if assessed using the ADL index and IADL scale [20]. Those scales have been identified as sensitive instruments to evaluate the functional status of elderly patients with neoplasm because that status can be related to chemotherapy tolerance/toxicity, disease progression/survival, and general health status [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The US National Center for Health Statistics estimated that 84% of noninstitutionalized individuals aged ≥65 years are dependent if assessed using the ADL index and IADL scale [20]. Those scales have been identified as sensitive instruments to evaluate the functional status of elderly patients with neoplasm because that status can be related to chemotherapy tolerance/toxicity, disease progression/survival, and general health status [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The field of geriatric oncology has increased in the western countries, although it is still in its early stages [12]. Several population-based studies have shown that elderly patients usually present with more advanced disease, however, few have stratified the elderly into different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Future trials should incorporate a comprehensive geriatric assessment to ameliorate the comparability of different trials and allow a more individualized treatment of elderly patients according to the patients' comorbidities and biologic age rather than biographical age. 31 This might also provide information on how the population studied in the trial compares with elderly HL patients in general and, more importantly, on how applicable this schedule might be right across the geriatric HL population.…”
Section: Discussionmentioning
confidence: 99%